A preference analysis of reinforcer variation and choice. Issue 3 (14th May 2021) - Hanratty, Laura A.; Hanley, Gregory P.
Abstract : Reinforcement procedures are the cornerstone of behavioral interventions. Previous research has focused on manipulating parameters of reinforcement including quality, magnitude, and rate. In this study, we sought to better understand ways to implement reinforcer choice and variation, and to assess preference for these parameters. Across 10 participants with and without disabilities, we assessed preference for varied reinforcement conditions, as well as choice of reinforcers in a concurrent‐chains arrangement. Most participants preferred varied reinforcement conditions and subsequently, choice of reinforcers, over a previously preferred varied reinforcement condition. Implications for reinforcement arrangement in teaching situations are discussed.